Test of export-led growth hypothesis: a comparative analysis on Turkey and newly developing countries - Kosekahyaoglu, Levent (Business: Theory and Practice, 2006)
The relation between exports and national income of a country has long been a frequently debated issue in both trade and growth theory. This issue is particularly important in providing arguments for ’free trade’ (export-led growth) or ‘protectionism‘ (import substitution) because presence of any causality between exports and income would imply supremacy of outward looking policies over inward looking policies. In order to test the export-led growth hypothesis, this work examines the relation between trade (exports and imports) and income for Turkey and seven newly developing countries using Granger causality analysis. Our results suggest that the export-led growth hypothesis is not supported only in cases of Argentina, and Brazil and that there is a strong unidirectional causality running from exports to growth for Turkey, the Czech Republic, Hungary, Poland, India and China.